THE LIVING LAW IN INDONESIA’S NEW CRIMINAL CODE: LEGAL PLURALISM, INDIGENOUS AUTONOMY, AND THE RISK OF STATE CO-OPTATION - Nikodemus Niko; Heni Widiyani; Fitri Kurnianingsih; Emmy Solina; Endri Endri; Angelo Lenard Yu; Syarifah Ema Rahmaniah (Faculty of Law, Universitas Diponegoro, 2026)
This study critically examines the incorporation of living law into Law Number 1 of 2023 concerning the Indonesian Criminal Code (KUHP), with particular attention to how the state defines, recognizes, and regulates legal norms originating from Indigenous and local communities. Although living law is often framed as a progressive instrument for accommodating legal pluralism, its formal inclusion in criminal law raises complex sociological concerns regarding the relationship between state authority and community-based normative systems. This study employs a qualitative socio-legal approach through critical analysis of statutory provisions, legal documents, and relevant scholarly debates on legal pluralism, customary law, and criminal law reform in Indonesia. The analysis shows that the recognition of living law in the new Criminal Code is not merely an acknowledgment of social norms that already exist within society. Instead, such recognition operates through state-defined criteria that determine which customary norms may be considered valid, legitimate, and enforceable within the formal criminal justice system. As a result, living law becomes a mechanism through which the state validates, regulates, and potentially absorbs Indigenous and local normative orders into the structure of national law. This process creates an ambivalent legal condition: while customary norms appear to gain formal recognition, their autonomy may be restricted by the requirements, classifications, and institutional procedures imposed by the state. This study argues that the incorporation of living law reflects not only an effort to recognize legal diversity, but also a broader strategy of governance that reinforces state control over legal plurality. The originality of this study lies in its sociological critique of living law as a regulatory instrument within contemporary Indonesian criminal law reform. By shifting the focus from formal recognition to power relations, this study contributes to debates on legal pluralism, Indigenous legal autonomy, and the politics of criminal law codification in Indonesia.